Molecular detection of Hydatid cyst isolated from Goats in AL-Qadisiyia province by Polymerase Chain Reaction - Mansoor Jadaan Ali Alkhaled (Kufa Journal for Veterinary Medical Sciences, 2015)
The present study was conducted during the period from August  2013 to April 2014 in AL-Qadisiyia province to detect the infection of hydatidiosis  in Goat using Molecular and conventional methods. One hundred and seventy nine  Goat  were examined at slaughters in Aldewanyia  abattoir. Caprinehydatid cyst were removed from infected  liver and lung after visceral inspection of these organs then  investigated the  viability of protoscolices by staining with eosin stain then examining under light microscope of 40x.The results showed 45 hydatid cyst were found from 179 goat  , the prevalence rate of infection (25.13%)  . 20 cyst were found fertile  only whereas 25 cyst were sterile. Regarding to infection site in organs, out of 45 hydatid cyst collected , 28(62.22%) cyst were isolated from liver whereas 17 (37.77%) isolated from lung with significant differences at p<0.05. Out of 45 hydatid cyst samples were taken from infected goats, and examined by conventional PCR , the PCR product demonstrated an expected fragment of 440 bp in the length , 10samples were given positive cases , 7(25%) samples from liver whereas only 3(12%) from lung samples gave positive  PCR  result, with statistically significant difference (P<0.05) between  two organs.